Dampak Sekolah Gratis terhadap Kualitas Pendidikan di SMA Negeri 1 Pagar Alam - Latifah Kurnia Utami; Afif Syaiful Mahmudin (Ideguru: Jurnal Karya Ilmiah Guru, 2024)
The importance of quality education in building a society that contributes to national development. The quality of education in Indonesia is currently still low. The problems often faced in the quality of education are economic factors and budget funds. Therefore, the government launched a compulsory education program and a free school program. This research aims to determine (1) the quality of education at SMA Negeri 1 Pagar Alam, (2) the positive and negative impact of free schools on the quality of education at SMA Negeri 1 Pagar Alam and (3) solutions to minimize the negative impact of free schools on the quality of education in Pagar Alam 1 Public High School. The method in this research is descriptive qualitative. The results of this research are (1) the quality of education is very good, seen in every component of education, both input, process and output, (2) the positive impact is to provide opportunities for students who are less fortunate but have good academic and non-academic achievements to learn. at SMA Negeri 1 Pagar Alam, while there is no negative impact on the quality of education, and (3) the solution to minimize the negative impact of free schools on the quality of education is by coordinating with parents and guardians, monitoring student success levels and utilizing available facilities and infrastructure. there is a maximum.